การพัฒนาแนวปฏิบัติการพยาบาลการดูแลเทาเพื่อปองกันการเกิดแผลที่เทาฯ Development of Nursing Practice Guideline for Foot Care and Wound Care in Older Persons with Diabetes Mellitus Attend Outpatient Department, Nongkungsri Hospital - Phukongchai, Monrat; Lertrat, Penchun (วารสารพยาบาลศาสตร์และสุขภาพ, 2014)
To develop a clinical nursing practice guideline for foot care prevention and wound care in olderpersons with diabetes mellitus, the model of the center for advanced nursing practice evidence -based by Soukup (2000) was used as a conceptual framework. Result revealed that older persons with diabetes mellitus foot care behaviors were inappropriate and nursing care was lacked of clinical practice guideline for foot care and wound care, Fourteen studies were including three systematic review and meta-analysis, two randomized controlled trial, two descriptive, one quasi-experimental study, two CNPGs and four CPGs. The content of this guideline was validated by five experts and the index of content validity was 0.93 and the evaluations of clarity of clinical nursing practice guideline feasibility were 100 %. The findings were revealed that patient foot care behaviors were improved. Further improved and update, outcome research to test the effectiveness of the clinical nursing practice guideline are suggested.